Language and Metaphysical Realism in Locke - Martín, Antoni Defez (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
According to Locke the corpuscular theory of matter was the best explanation of the reality.Nevertheless, he did not believe that it was possible to demonstrate philosophically the truth of thisclaim: human beings can only achieve justified beliefs, but not knowledge, on the actual constitution ofthe world. For this reason, Locke, in his philosophical defense of the corpuscular hypothesis, appealsto theology: God could make possible what for human beings would be inconceivable.
Keywords: Locke; corpuscular theory; materialism; reality; knowledge; theology